Non-pharmacological treatments of inpatients with major depression – The case of Polish (Poznan) and German (Kiel) hospital. (May 2020) - Zaprutko, Tomasz; Göder, Robert; Rybakowski, Filip; Kus, Krzysztof; Kopciuch, Dorota; Paczkowska, Anna; Ratajczak, Piotr; Nowakowska, Elżbieta
Abstract: Background and purpose: Although the treatment of depression should be comprehensive, there is insufficient information about non-pharmacological interventions used during hospitalization. Hence, the aim was to compare non-pharmacological interventions used in psychiatry clinics in Kiel (Germany) and Poznan (Poland). Methods and materials: The retrospective study covered all patients hospitalized in 2016 (F32 or F33). Out of 545 patients hospitalized in 2016 in both centers, the analysis concerns 322 records from Kiel and 168 from Poznan. Results: Non-pharmacological treatments were used in both centers. However, in Kiel there were more therapeutic options. Contrary to Poznan, patients in Kiel used therapies like "Kneippen", Qigong, and light therapy. Conclusions: Implementing Tai Chi in Kiel would be interesting to develop the scope of used interventions. Investment in non-pharmacological treatment should be a priority for healthcare decision-makers in Poland. The wide range of non-pharmacological interventions should be commonly accessible to provide the most comprehensive treatment. Highlights: Depression is the leading reason for significant disability, has a negative impact on the quality of life. Complementary therapies should support pharmacotherapy of depression. Several non-pharmacological interventions might be a crucial part of a comprehensive therapy. Therapies like Tai Chi, Qigong, or "Kneippen" might be effectively incorporated in the treatment of depression.